Enamel caries resistance accidentally irradiated by the Nd : YAG laser - de Andrade, L. E. H.; Lizarelli, R.; Pelino, J. E. P.; Bagnato, V S; Oliveira, O. B. de (Wiley-Blackwell, 2007)
When the carious tissue is eliminated either by conventional methods (with burs) or with lasers, the risk of accidentally damage the surface of adjacent teeth may occur, which hypothetically could lead to a more susceptible surface for canes formation. This in vitro study aims to evaluate the caries resistance of the dental enamel surface irradiated by the Nd:YAG laser applied in conditions simulating accidental exposition. Thirteen third molars were used in this study. The experimental groups were: G1: sound control and control + carious; G2: contact Nd:YAG laser at 0.75, 1, 2, or 3 W; 10 Hz; 3 sec (27, 35, 71, and 106 J/cm(2)); G3: same parameters from G2 + caries artificial induction through the demineralization and demineralization (DES/RE) dynamic model. The caries resistance analysis was evaluated by the superficial morphological aspect through SEM images and also by Ca/P proportion through energy dispersive X-ray spectroscopy (EDX). The micrograph images showed that the Nd:YAG laser changed the normalmorphology of the enamel prisms resulting in a melted and re-solidified surface intensified with the power increase. Significant statistical differences were observed applying the Kruskal-Wallis statistical test (p <= 0.01) among the Nd:YAG laser irradiated groups and the control with caries regarding the Ca/P proportion. As an exception, this was not observed when 3 W; 10 Hz; 3 sec; 106 J/cm(2) was applied and posteriously submitted to a cariogenic challenge. The results indicate that the Nd:YAG laser accidental irradiation at low power settings did not represent risks to the enamel caries resistance.
Keywords: Nd : YAG laser; dental enamel; dental caries susceptibility